Late-Onset Puberty Induction by Transdermal Estrogen in Turner Syndrome Girls—A Longitudinal Study - Gawlik, Aneta Monika; Hankus, Magdalena; Szeliga, Kamila; Antosz, Aleksandra; Gawlik, Tomasz; Soltysik, Kamil; Drosdzol-Cop, Agnieszka; Wilk, Krzysztof; Kudela, Grzegorz; Koszutski, Tomasz; Malecka-Tendera, Ewa (Frontiers in Endocrinology, 2018)
Objective: Estrogen replacement therapy (ERT) for Turner syndrome (TS) is a widely discussed topic; however, the optimal model of ERT for patients with delayed diagnosis and/or initiation of therapy is still unclear, mainly due to insufficient data. We present the results of a prospective observational single center study in which the efficacy of late onset puberty induction by one-regimen transdermal ERT in TS girls was evaluated. Methods: The analysis encompassed 49 TS girls (63.3% with 45,X) with hypergonadotropic hypogonadism in whom unified transdermal ERT protocol was used for puberty induction (first two months 12.5 µg/24h, thereafter 25.0 µg/24h until breakthrough bleeding). Clinical visits for examination and therapy modification took place every 3-6 months. Transabdominal pelvic ultrasound examinations were performed at least twice: at the beginning and at the end of follow-up. Results: The mean (SD)/median (range) age at ERT induction was 15.1 (1.3)/15 (11.7-17.8) years. The duration of follow-up was 2.4 (1.1)/2.2 (1.0-6.2) years. Half of all the patients had at least B2 after 0.57 yrs., B3 after 1.1 yrs., B4 after 1.97 yrs. and menarche after 1.82 year from ERT initiation. In earlier initiation of ERT (≤14 yrs.), B2 (p=0.059) was achieved faster and B4 (p=0.018) significantly slower than in later start of ERT. 34 (94.4%) patients had at least stage B3 at menarche. The karyotype, initial weight and BMI had no impact on puberty tempo during ERT. The uterine volume increased significantly during ERT in all the study group (p<0.0001), and in half of the patients the increase was at least 12.4-fold. It did not correlate with the duration of treatment (p=0.84) or dose of estradiol per kg (p=0.78), nor did it depend on karyotype (p=0.71) or age at ERT initiation (p=0.28). There were no differences in ∆hSDS during ERT (p=0.63) between the two age groups (ERT ≤14 and >14 yrs.). Conclusions: The presented fixed-dose regime for late onset puberty induction allowed for a satisfactory rate of achieving subsequent puberty stages and did not influence the growth potential. In the context of compliance, this model of ERT was easy to use and well accepted by the patients.